EXPRESSION OF TLR2, TLR3, TLR4 AND PROINFLAMMATORY TNF AND IL-6 CYTOKINES IN LIVER BIOPSIES OF NONALCOHOLIC FATTY LIVER DISEASE PATIENTS - A. V. Bogolyubova; E. E. Mishina; P. O. Bogomolov; M. V. Matsievich; K. Yu. Kokina; A. Yu. Mayorov; P. V. Belousov (Медицинская иммунология, 2019)
Non-alcoholic fatty liver disease (NAFLD) is a group of conditions closely associated with obesity that are among the most common and socially significant liver diseases in the modern Western world. The emergence and progression of NAFLD from simple steatosis to non-alcoholic steatohepatitis with the subsequent development of fibrosis are the leading factors in the pathogenesis of a significant proportion of the most severe liver pathologies, such as cirrhosis and hepatocellular carcinoma, as well as extrahepatic metabolic complications of NAFLD, such as insulin resistance and type 2 diabetes mellitus. The inflammatory component is one of the most important factors in the pathogenesis of NAFLD, particularly in the context of the progression of simple steatosis to non-alcoholic steatohepatitis. At the same time, the role of the most important mediators of the inflammatory response, innate immunity receptors and the Toll-like receptors in particular, in the pathogenesis of NAFLD has been poorly studied. In the present work, we first used the bioinformatics analysis of the publicly available gene expression databases to demonstrate that only TLR1, TLR2, TLR3 and TLR4 were significantly expressed in the healthy human liver. We then used the reverse transcription PCR to measure the mRNA expression levels of TLR2, TLR3, and TLR4, as well as those of the important pro-inflammatory mediators tumor necrosis factor (TNF) and interleukin-6 (IL-6), in the liver biopsy specimens obtained from 20 patients with NAFLD (simple steatosis, n = 10; non-alcoholic steatohepatitis, n = 10), as well as from 4 obese patients with clinical suspicion for NAFLD but no histological signs of NAFLD in their liver biopsies. We found a significant increase in the expression of TLR2, TLR3 and TLR4 mRNA in liver biopsy samples obtained from patients with non-alcoholic steatohepatitis as compared to those obtained from controls without histological signs of NAFLD. We were also able to demonstrate the association between the hepatic levels of TLR2, TLR3 and TLR4 mRNAs with the histological degree of liver damage as evidenced by the degree of steatosis and balloon dystrophy of hepatocytes, as well as with the plasma levels of uric acid, the important endogenous stimulator of innate immunity. Our data indicate the possible involvement of innate immunity, particularly the Toll-like receptors, in the pathogenesis of NAFLD.